1983
DOI: 10.1029/gl010i008p00686
|View full text |Cite
|
Sign up to set email alerts
|

Crosshole seismology and seismic imaging in crystalline rocks

Abstract: A borehole‐to‐borehole audiofrequency seismic system using piezoelectric transducers as active elements has been developed and used to investigate crystalline rocks in Canada. High‐quality seismograms have been recorded for transmitter‐receiver distances of up to 230 meters. It has been found that both travel times and signal amplitudes provide diagnostic information about rock quality. Two‐dimensional images of seismic velocity and transparency distributions between two boreholes, derived from observed arriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…Downhole seismic surveys such as side scan, VSP and mine seismic profiling (MSP), and in-mine seismic surveys are best suited for imaging steeply dipping to subvertical structures (e.g., Price, 1974;Cosma, 1983;Wong et al, 1983Wong et al, , 1984Gustavsson et al, 1984;Galperin, 1985;Peterson et al, 1985;Spathis et al, 1985;Harman et al, 1987;Mutyorata et al, 1987;Duncan et al, 1989;Juhlin et al, 1991;Sinadinovski et al, 1995;Frappa and Moinier, 1993;Cao and Greenhalgh, 1997;Greenhalgh and Bierbaum, 1998;Urosevic and Evans, 2000;Greenhalgh et al, 2000Greenhalgh et al, , 2003Wong, 2000;Adam et al, 2003;Cosma et al, , 2007Perron et al, 2003;Bellefleur et al, 2004aBellefleur et al, , 2004bXu and Greenhalgh, 2010). They have typically higher resolution than surface seismic data, which make them attractive for delineating fracture and fault zones for mine planning or as a complement to surface seismic surveys.…”
Section: Seismic Methods For Mineral Exploration Wc175mentioning
confidence: 99%
See 1 more Smart Citation
“…Downhole seismic surveys such as side scan, VSP and mine seismic profiling (MSP), and in-mine seismic surveys are best suited for imaging steeply dipping to subvertical structures (e.g., Price, 1974;Cosma, 1983;Wong et al, 1983Wong et al, , 1984Gustavsson et al, 1984;Galperin, 1985;Peterson et al, 1985;Spathis et al, 1985;Harman et al, 1987;Mutyorata et al, 1987;Duncan et al, 1989;Juhlin et al, 1991;Sinadinovski et al, 1995;Frappa and Moinier, 1993;Cao and Greenhalgh, 1997;Greenhalgh and Bierbaum, 1998;Urosevic and Evans, 2000;Greenhalgh et al, 2000Greenhalgh et al, , 2003Wong, 2000;Adam et al, 2003;Cosma et al, , 2007Perron et al, 2003;Bellefleur et al, 2004aBellefleur et al, , 2004bXu and Greenhalgh, 2010). They have typically higher resolution than surface seismic data, which make them attractive for delineating fracture and fault zones for mine planning or as a complement to surface seismic surveys.…”
Section: Seismic Methods For Mineral Exploration Wc175mentioning
confidence: 99%
“…However, the only surface method that can provide high-definition images of the underground and has the required depth of penetration is the seismic reflection method. The potential of the method for mine planning and exploration has been long known (e.g., Schmidt, 1959;Oblogina et al, 1962;Elliot, 1967;Gupta, 1971;Reid et al, 1979;Hawkins and Whiteley, 1980;Kehrman, 1980;Ruskey, 1981;Wright, 1981;Gladwin, 1982;Nelson, 1980Nelson, , 1984Cosma, 1983;Wong et al, 1983;Campbell and Peace, 1984;Gustavsson et al, 1984;Dahle et al, 1985;Galperin, 1985;Fatti, 1987;Mutyorata, 1987;Campbell and Crotty, 1988;Duncan, 1989;Pretorius et al, 1989;Read, 1989;Young et al, 1989;Gendzwill, 1990;Juhlin et al, 1991;Maxwell and Young, 1992;Milkereit et al, 1992c;Spencer et al, 1993;Cao and Greenhalgh, 1995;Frappa and Moinier, 1993;Friedel et al, 1995Friedel et al, , 1996Milkereit et al, 1996;Salisbury et al, 1996;Greenhalgh and Mason, 1997;Hajnal et al, 1997;…”
Section: Introductionmentioning
confidence: 99%
“…Based on these effects, several studies have shown the potential for using seismic tomography and vertical seismic profiling (VSP) techniques for the location and charaterization of fractures in a rock mass (Peterson et al, 1985;Wong et al, 1983;Crampin, 1985;.l\lajer et al, 1987;and others). The observed effects of fractures on seismic wave amplitudes can be an order of magnitude greater than the effects on velocities (King et al, 1986).…”
Section: Lntroducflonmentioning
confidence: 99%
“…McKenzie et a1 [7] and Gladwin [8] employed cross-hole ultrasonic measurements to characterize the degree of fracturing in a rock mass, and to monitor stress changes in the pillars of underground mines. Recently, Wong et a1 [9] have reported acoustic crosshole measurements in crystalline rocks, that were used to infer changes in lithology and to trace fracture zones between boreholes. The field system employed is shown in diagrammatic form in Fig.…”
Section: Introductionmentioning
confidence: 99%